The bookshop of yesterdays - Meyerson, Amy (Park Row Books, 2019)
Miranda Brooks grew up in the stacks of her eccentric Uncle Billy<U+2019>s bookstore, solving the inventive scavenger hunts he created just for her. But on Miranda<U+2019>s twelfth birthday, Billy has a mysterious falling-out with her mother and suddenly disappears from Miranda<U+2019>s life. She doesn<U+2019>t hear from him again until sixteen years later when she receives unexpected news: Billy has died and left her Prospero Books, which is teetering on bankruptcy<U+2014>and one final scavenger hunt. When Miranda returns home to Los Angeles and to Prospero Books<U+2014>now as its owner<U+2014>she finds clues that Billy has hidden for her inside novels on the store<U+2019>s shelves, in locked drawers of his apartment upstairs, in the name of the store itself. Miranda becomes determined to save Prospero Books and to solve Billy<U+2019>s last scavenger hunt. She soon finds herself drawn into a journey where she meets people from Billy<U+2019>s past, people whose stories reveal a history that Miranda<U+2019>s mother has kept hidden<U+2014>and the terrible secret that tore her family apart.